BaTiO3–CoFe2O4–BaTiO3 trilayer composite thin films prepared by chemical solution deposition. Issue 3 (February 2016) - Walther, Till; Quandt, Norman; Köferstein, Roberto; Roth, Robert; Steimecke, Matthias; Ebbinghaus, Stefan G.
Abstract: Multiferroic BaTiO3 –CoFe2 O4 –BaTiO3 thin films were synthesized by spin coating of Co(NO3 )2 –Fe(NO3 )3 and Ba(OAc)2 –Ti( i -OPr)4 dissolved in a mixture of acetic acid and dimethylformamide. Stepwise thermal treatment at 200, 400 and 800 °C led to the desired phases. The phase formation process was monitored by thermoanalytic, XRD, IR and Raman measurements. SEM was used to characterize the structure and thickness of each layer. Two samples with different thicknesses of perovskite and spinel layers are discussed. Sample1 consists of 120 nm CoFe2 O4 between two 70 nm BaTiO3 layers. For sample2, the 90 nm BaTiO3 top and bottom layers are enclosing 220 nm CoFe2 O4 . The surface qualities were determined by AFM indicating rms roughness values of about 4 nm. Magnetic investigations reveal slightly anisotropic behavior. Polarization measurements show hysteresis loops ( P S(max) = 29 μC cm −2 ; P R(max) = 17 μC cm −2 ) with switching peaks at the corresponding coercive fields.